Two versions of the medieval model of the “symphony” of church-state relations - Georgy Bezhanidze (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The word ???????? is found in two of the most important collections of Byzantine law: novellas and the Eisagoge, where it takes on diff erent meanings. The article analyses the preamble to the sixth novella, the Eisagoge, as well as other medieval texts to establish the meaning of the concept of the “symphony of the kingdom and the priesthood”. The author shows that two diff erent versions of the “symphony” were formed in Byzantium. According to St. Justinian the Great, good harmony, capable of providing all kinds of benefi ts to the human race, does not depend on the relationship between state and church authorities. The “imperial” model of a symphony arises when the kingdom and priesthood properly fulfi ll their ministry before God. The Emperor is obliged to justly rule the Orthodox people, take care of the clergy, and monitor the observance of dogmata and canons. The role of the priesthood is reduced to prayer and the performance of the Sacraments. The second version of the symphony, refl ected in the Eisagoge, on the contrary, involves communication between representatives of the kingdom and the priesthood. The harmony of the two powers is identifi ed with the agreement between the emperor and the patriarch. Only the Patriarch of Constantinople can play such a role. Other hierarchs, including the Eastern Patriarchs, do not matter for achieving “peace and prosperity for the Christian people”. As it is shown in the article, such a separation of the Patriarch of Constantinople from the episcopate can be compared with the ecclesiological model of Roman Catholicism, and the “symphony” of the priesthood and kingdom, presented in Isagogue, with the Latin concept of “the pope behind the back of the emperor”.